Estudo in silico e in vitro da atividade antifúngica do p-cumarato de 4-clorobenzila sobre Candida spp. - Melo, Ana Karoline Vieira (2021)
Objetive: To evaluate the antifungal activity of p-coumarate of 4-chlorobenzyl, na unprecedented semi-synthetics molecule, Against 16 Candida species. Methodology: Molecular docking and tests to determine the Minimum Inhibitory Concentration (MIC) and Minimum Fungicidal Concentration (MFC) were carried out; Mechanism of action on Sorbitol and Ergosterol; Growth kinetics; Death kinetics; Result of the association between drugs (Checkerboard); Effects on biofilm, micromorphology na human keratinocytes (HaCaT). Results: Molecular docking indicated affinity between p-coumarate of 4-chlorobenzyl and all selected antifungal targets, especially with the thymidylated synthase enzyme (5UIV) with binding energy: -130.96 Kcal.mol-1. The MIC and MFC against the 16 strains ranged from 3.9 μg/mL (13,54 μM) a 62.5 μg/mL (217,01 μM). In the presence of Ergosterol, the MIC increased from 7.8 μg/mL (27,1 μM) para 250 μg/mL (867,8 μM), suggesting a probable mechanism of action on the molecule, involving the fungal plasma membrane. However, with the addition of Sorbitol, the MIC remained unchanged. The p-coumarate of 4-chlorobenzyl inhibited fungal growth from the 1st hour of testing. In the death kinetics assay, the molecule inhibited fungal growth until the 23rd hour of incubation. The association of the molecule with Nystatin proved to be indifferent. There was a 69% reduction in the already formed biofilm at a concentration of 40μg/mL (138,86 μM) ((p<0,0001)). The molecule promoted changes in fungal micromorphology reducing the extension and frequency of pseudohyphae. In the assay with keratinocytes, the molecule had an IC50 7.90 ± 0.40 μg/mL (27,45 ± 1,42 μM). Conclusion: Docking revealed affinity prediction between p-coumarate of 4-chlorobenzyl and all tested fungal targets, with strong bioactivity, being a fungicide for all 16 strains tested; with a probable mechanism of action on the fungal plasma membrane; with fast onset and long duration of action; being indifferent when associated with Nystatin; reducing biofilm; changing the fungal micromorphology and presenting toxicity on HaCaT, however, 100x lower than Doxorubicin.